Forecasting the Utility of Smart Phones and its Usage Behaviour amongst the Management Students in Mumbai - Kishore , Minakshi; KM, Kavita; Sharma, Priyanka (Gyan Management Journal, 2015)
The purpose of this exploratory study is to better understand the current dynamics of the Mumbai market for smart-phones and the usage behaviours of consumers. This paper presents the result of a survey on the trend of smart-phone from the perspective of end consumers. The data was collected from 283 respondents across Mumbai. This study has looked into the familiarity of users towards smart· phones, choices of smart-phone brand and service providers, and most importantly the determinants that influence their purchasing decision. Additionally, the consumers' preferences on smart-phone specifications such as design, computing power, operating platform, and price
Keywords: Mobile phone; Smartphone; Usage behaviour; Market survey; Consumers study